Analysis of Borax Contaminants in Sempol Snacks in Gonilan Village Kartasura - Nuzulia Sari Asyifa’; Reni Ariastuti; Fadilah Qonitah (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2022)
Sempol is a snack made from processed meat that is quite popular among the public. In its manufacture, there is still a lot of misuse of prohibited additives, one of which is borax, in order to obtain a more supple shape and a longer shelf life. This study aims to determine the content and levels of borax in sempol snacks circulating in Gonilan Kartasura Village. The methods used in this study were qualitative using turmeric paper and quantitative using UV-Vis spectrophotometry. The results of the qualitative study showed that of the 7 samples of sempol snacks, there were 2 that positively contained borax, namely samples F and G. The quantitative results showed that the level of borax in sample F was 101,55±0,75 mg/g and in sample G was 166,69±0,67 mg/g. KEYWORDS: Borax; Sempol; UV-Vis Spectrophotometry